Solid-state batteries with aluminum-based anodes
Solid-state batteries with aluminum-based anodes and solid electrolytes address the limitations of conventional lithium-ion batteries by enhancing energy density, safety, and sustainability, while eliminating the need for liquid electrolytes.
Patent Information
- Application Number
- JP2024559225
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional lithium-ion batteries face limitations in energy density and safety due to the use of graphite anodes and liquid electrolytes, which can lead to dendrite formation and flammability issues.
The development of solid-state batteries utilizing aluminum-based anode materials and solid electrolytes, which offer higher lithium capacity, improved safety, and reduced environmental impact by eliminating the need for liquid electrolytes.
The use of aluminum-based anodes and solid electrolytes in solid-state batteries enhances energy density, safety, and sustainability, while minimizing the formation of solid electrolyte interfaces and reducing the risk of flammability.
Smart Images

Figure 2025513787000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Provisional Patent Application No. 63 / 362,722, filed April 8, 2022, and entitled SOLID-STATE BATTERIES WITH ALUMINUM-BASED ANODES, the contents of which are incorporated herein by reference in their entirety.
[0002] The present disclosure relates generally to metallurgy, and more specifically, to solid-state batteries including aluminum-based anode active materials. [Background technology]
[0003] A conventional lithium-ion battery generally includes a cathode, an anode, and a separator between the cathode and the anode, which is immersed in an electrolyte. The cathode and anode current collectors are used to conduct electrical current between the cathode and the anode, while the electrolyte allows the lithium ions to transport between the cathode and the anode. Due to the electrical potentials involved, copper is generally used as the anode current collector, and aluminum is generally used as the cathode current collector. Lithium metal oxides, such as lithium cobalt oxide, are generally used as lithium-ion battery cathodes, and graphite is generally used as lithium-ion battery anodes. Summary of the Invention
[0004] The terms embodiments and similar terms are intended to broadly refer to all of the subject matter of the present disclosure and the claims that follow. Statements containing these terms should be understood to neither limit the subject matter described herein nor limit the meaning or scope of the claims that follow. The embodiments of the present disclosure addressed herein are defined by the claims that follow, and not by this summary. This summary is a high level overview of various aspects of the present disclosure and introduces some of the ideas that are further described in the Detailed Description section below. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used alone to determine the scope of the claimed subject matter. The subject matter should be understood by reference to the entire specification of this disclosure, any or all drawings, and appropriate portions of each claim.
[0005] In various aspects, a solid-state battery or electrochemical cell is described herein. The solid-state battery described herein is useful as an alkali metal alloyed anode and includes an aluminum-based anode material that is different from the anodes used in conventional lithium-ion batteries and solid-state batteries. The aluminum-based alkali metal alloyed anode can exhibit a much higher lithium capacity than conventional anode materials such as graphite. For example, the aluminum-based alkali metal alloyed anode can incorporate lithium atoms within the aluminum crystalline matrix. This means that more lithium can be incorporated per unit volume compared to an equivalent amount of graphite in which the lithium atoms are intercalated and housed between the graphite layers. In this way, the size and / or mass of the anode can be reduced compared to conventional graphite anodes while maintaining or increasing the overall capacity. In some examples, the solid-state batteries described herein may have a capacity of 300mAh / g to 350mAh / g, 350mAh / g to 400mAh / g, 400mAh / g to 450mAh / g, 450mAh / g to 500mAh / g, 500mAh / g to 550mAh / g, 550mAh / g to 600mAh / g, 600mAh / g to 650mAh / g, 650mAh / g The anode may include an anode exhibiting a specific capacity of 300 mAh / g to 1000 mAh / g, such as 700 mAh / g to 750 mAh / g, 750 mAh / g to 800 mAh / g, 800 mAh / g to 850 mAh / g, 850 mAh / g to 900 mAh / g, 900 mAh / g to 950 mAh / g, or 950 mAh / g to 1000 mAh.
[0006] Additionally, the solid-state batteries described herein include a solid-state electrolyte that is distinct from and offers several advantages over conventional liquid electrolytes: Because both the solid-state electrolyte and the aluminum-based anode can be assembled to create a solid-state battery as solid materials along with the prepared cathode material, the combination of the aluminum-based anode and the solid-state electrolyte can be further advantageous by reducing or eliminating the handling of solutions or liquids during various manufacturing steps.
[0007] In some examples, the solid-state battery may include an anode, such as an anode including aluminum as an anode active material, a cathode, and a solid electrolyte between the anode and the cathode. For example, the anode may include an aluminum-based alkali metal alloyed anode, such as when the alkali metal is lithium. Optionally, the anode includes an aluminum alloy or a recycled content aluminum alloy. The use of a recycled content aluminum alloy may, for example, help to increase the sustainability of the solid-state battery or reduce the total carbon footprint associated with the solid-state battery.
[0008] In examples, the anode may include or be in the form of a foil, such as an aluminum-based multicomponent foil. In some examples, the anode has a thickness of 5 μm to 60 μm, such as 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 20 μm to 25 μm, 25 μm to 30 μm, 30 μm to 35 μm, 35 μm to 40 μm, 40 μm to 45 μm, 45 μm to 50 μm, 50 μm to 55 μm, or 55 μm to 60 μm.
[0009] Optionally, the aluminum-based multi-component foil may include aluminum or an aluminum alloy and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver. It should be understood that aluminum-based anodes may undergo volume changes during lithium absorption and release, and these non-aluminum elements may enhance the ability of aluminum to be used as an alloyed anode, such as by providing structural integrity and / or a conductive base to the alloyed anode. In some examples, the anode includes a foil including 40% to 99% by weight aluminum or an aluminum alloy and 30% to 60% by weight one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver. For example, the anode can include aluminum or aluminum alloy in an amount of 40% to 45% by weight, 45% to 50% by weight, 50% to 55% by weight, 55% to 60% by weight, 60% to 65% by weight, 65% to 70% by weight, 70% to 75% by weight, 75% to 80% by weight, 80% to 85% by weight, 85% to 90% by weight, 90% to 95% by weight, or 95% to 99% by weight. Optionally, the anode may include one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver in a total amount of 30% to 35%, 35% to 40%, 40% to 45%, 45% to 50%, 50% to 55%, or 55% to 60% by weight. In some examples, the aluminum alloy is a brazing alloy.
[0010] In some examples, the anode comprises a composite foil, such as comprising a first plurality of aluminum or aluminum alloy particles and a second plurality of particles selected from at least one of metal particles or non-metal particles. Useful metal or non-metal particles may include elements other than aluminum, such as silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
[0011] Any suitable solid electrolyte may be used with the solid-state batteries described herein. For example, the solid electrolyte may be or may include an inorganic solid electrolyte. However, other solid electrolytes, such as polymer solid electrolytes or gel polymer electrolytes, may also be used. Optionally, the solid electrolyte may be a lithium silver germanium sulfide material, Li 6 P.S. 5 Cl, Lithium superionic conductor (LISICON), doped garnet material, Li 7 La 3 Zr 2 O 12 (LLZO), Li 10 GeP 2 S 12 , Li 10 SnP 2 S 12 , lithium phosphate sulfide (Li 3 P.S. 4 ), or lithium oxynitride phosphorus acid (LIPON). The solid electrolyte may have any suitable thickness. In examples, the solid electrolyte may have a thickness of about 10 μm to about 300 μm, such as 10 μm to 20 μm, 20 μm to 30 μm, 30 μm to 40 μm, 40 μm to 50 μm, 50 μm to 75 μm, 75 μm to 100 μm, 100 μm to 125 μm, 125 μm to 150 μm, 150 μm to 175 μm, 175 μm to 200 μm, 200 μm to 225 μm, 225 μm to 250 μm, 250 μm to 275 μm, or 275 μm to 300 μm.
[0012] Any suitable cathode can be used with the solid-state batteries described herein. For example, the cathode can include an alkali ion host material or an alkali metal-transition metal oxide cathode active material. Optionally, the cathode can include lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, lithium cobalt oxide, conversion cathode, FeS 2 , FeF 3 , a sulfur-based cathode, or may include sulfur.
[0013] Other suitable components can optionally be included in the solid-state batteries described herein. For example, the solid-state battery can further include one or more of a cathode current collector in contact with the cathode or an anode current collector in contact with the anode. Optionally, the anode current collector and / or the cathode current collector comprises a protected aluminum alloy foil. Optionally, the anode current collector comprises a copper foil.
[0014] In some examples, the anode, solid electrolyte, and cathode are in a stack with pressure applied therebetween. For example, the stack pressure applied between the anode and cathode may be from about 0.1 MPa to about 30 MPa, such as 0.1 MPa to 0.5 MPa, 0.5 MPa to 1 MPa, 1 MPa to 2 MPa, 2 MPa to 3 MPa, 3 MPa to 4 MPa, 4 MPa to 5 MPa, 5 MPa to 7.5 MPa, 7.5 MPa to 10 MPa, 10 MPa to 12.5 MPa, 12.5 MPa to 15 MPa, 15 MPa to 17.5 MPa, 17.5 MPa to 20, 20 MPa to 22.5 MPa, 22.5 MPa to 25 MPa, 25 MPa to 27.5 MPa, or 27.5 MPa to 30 MPa.
[0015] In another example, another component that may be optionally included is an interface material. For example, the solid-state battery may further include an interface material between the anode and the solid electrolyte. Optionally, the interface material includes a solid electrolyte interface, an artificial solid electrolyte interface, a polymer coating, a carbon coating, or an inorganic coating.
[0016] In another embodiment, a method for manufacturing a solid-state battery or electrochemical cell is described herein. An exemplary method of this embodiment includes providing an anode including aluminum as an anode active material, providing a cathode, and disposing a solid electrolyte between the anode and the cathode. The method of this embodiment may include, or may further include, contacting the anode with an anode current collector or contacting the cathode with a cathode current collector.
[0017] Optionally, providing the anode includes preparing an aluminum-based multi-component foil, such as an aluminum-based multi-component foil including aluminum or an aluminum anode and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
[0018] Various methods can be used to prepare the aluminum-based multi-component foil. In some examples, preparing the aluminum-based multi-component foil includes casting an aluminum-based multi-component product including aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to produce an aluminum-based multi-component product, and rolling the aluminum-based multi-component product into a foil. In some examples, preparing the aluminum-based multi-component foil includes obtaining a powder mixture of aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver, and subjecting the powder mixture to a laser powder bed fusion process to produce an aluminum-based multi-component product. In some examples, preparing the aluminum-based multi-component foil includes cumulatively roll-bonding aluminum or an aluminum alloy with a quantity of one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to produce an aluminum-based multi-component product. In some examples, preparing the aluminum-based multi-component foil includes forming a microporous or nanoporous aluminum-based multi-component product using powder metallurgy, additive manufacturing, metal foam, forming perforations by laser or deep etching, dealloying (e.g., chemical dealloying), or other methods. Optionally, preparing the aluminum-based multi-component foil includes or further includes rolling the aluminum-based multi-component product into a foil.
[0019] Other objects and advantages will become apparent from the following detailed description of non-limiting examples.
[0020] DETAILED DESCRIPTION OF THE DRAWINGS This specification refers to the following accompanying drawings, in which the use of like reference numbers in different drawings is intended to indicate like or similar components. [Brief description of the drawings]
[0021] [Figure 1] 1 shows a schematic overview of an exemplary method for producing a rolled aluminum alloy product. [Diagram 2] FIG. 1 shows a schematic diagram of an exemplary solid-state electrochemical cell including an anode comprising aluminum as the anode active material. [Diagram 3] FIG. 1 shows a schematic diagram of an exemplary solid-state electrochemical cell including an anode comprising aluminum as the anode active material and a protected aluminum anode current collector. [Figure 4] 1 provides data showing exemplary cell cycling data for a first exemplary solid-state electrochemical cell. [Diagram 5] 1 provides data showing cycling capacity data for a first exemplary solid-state electrochemical cell. [Figure 6] 1 provides data showing coulombic efficiency data for a first exemplary solid-state electrochemical cell. [Figure 7] 13 provides data showing exemplary cell cycling data for a second exemplary solid-state electrochemical cell. [Figure 8] 1 provides data showing cycling capacity data for a second exemplary solid-state electrochemical cell. [Figure 9] 13 provides data showing coulombic efficiency data for a second exemplary solid-state electrochemical cell. [Figure 10] 1 provides data showing exemplary cell cycling data for an exemplary reference half-cell using a liquid electrolyte. [Figure 11] 1 provides data showing cell capacity data for an exemplary reference half-cell using a liquid electrolyte. [Figure 12] 13A-13C are data showing coulombic efficiency data for an exemplary reference half-cell using liquid electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Described herein are solid-state electrochemical cells incorporating solid electrolytes and aluminum materials as the anode active material. The use of aluminum as the anode active material can promote increased energy density and specific energy compared to cells using traditional anode materials (e.g., graphite), improved safety of secondary batteries compared to cells using lithium metal anodes or compared to cells using liquid electrolytes, and avoids, at least for the anode side, wet processing, the use of liquid solvents during manufacture, and the use of liquid electrolytes.
[0023] The aluminum anode active material can include an alkali metal alloyed anode. For example, lithium can be alloyed with aluminum at low potential, and lithium ions can be reduced and incorporated as an alloy into the bulk of the aluminum material. The aluminum used in the anode active material can be a foil (e.g., a composite foil or alloy foil), such as a foil that includes aluminum or an aluminum alloy, and optionally includes one or more other elements, such as silicon, tin, indium, gallium, antimony, lead, nickel, copper, zinc, carbon, germanium, silver, in an amount of 0.5 mol % to 50 mol %. The foil can be or include a eutectic alloy, a solid solution alloy, a mixed alloy system, or a composite particle system. As described herein, the foil can be processed using metal casting and metal rolling processes, but other techniques, including powder-based sintering processes, or laser melting processes, such as laser powder bed melting techniques, can also be used to prepare the foil. Additionally, foils can be prepared to have engineered structures, for example, by powder metallurgy techniques, forming micro- or nano-porous structures by additive manufacturing, using metal foams, forming perforations by laser or deep etching, dealloying (e.g., chemical dealloying), or using other methods. In some examples, metal products prepared by powder-based or engineered processes can be subjected to rolling to at least partially consolidate the foil and / or to produce foils from the metal products.
[0024] Definitions and Explanations As used herein, the terms "invention," "the invention," "this invention," and "the present invention" are intended to refer broadly to all of the subject matter of this patent application and the claims that follow. Statements containing these terms should be understood in no way to limit the subject matter described herein, nor to limit the meaning or scope of the claims that follow.
[0025] In this description, reference will be made to aluminum alloys identified by AA numbers and other associated designations (e.g., "series" or "7xxx"). To understand the numbering systems most commonly used in naming and identifying aluminum and its alloys, please see "International Alloy Designations and Chemical Composition Limits for Wrought Aluminum and Wrought Aluminum Alloys," or "Registration Record of Aluminum Association Alloy Designations and Chemical Composition Limits for Aluminum Alloys in the Form of Castings and Ingot" (both published by The Aluminum Association).
[0026] As used herein, a plate is generally greater than about 15 mm in thickness. For example, a plate may refer to an aluminum product having a thickness of greater than about 15 mm, greater than about 20 mm, greater than about 25 mm, greater than about 30 mm, greater than about 35 mm, greater than about 40 mm, greater than about 45 mm, greater than about 50 mm, or greater than about 100 mm.
[0027] As used herein, a shade (also called a sheet plate) generally has a thickness of about 4 mm to about 15 mm. For example, the shade may have a thickness of about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, about 12 mm, about 13 mm, about 14 mm, or about 15 mm.
[0028] As used herein, sheet generally refers to an aluminum product having a thickness of less than about 4 mm. For example, the sheet may have a thickness of less than about 4 mm, less than about 3 mm, less than about 2 mm, less than about 1 mm, less than about 0.5 mm, or less than about 0.3 mm (e.g., about 0.2 mm). As used herein, foil includes a subset of sheets and generally has a thickness of less than about 200 μm. In some examples, the foil may have a thickness of about 10 μm to about 200 μm, such as about 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, or 200 μm.
[0029] In this application, alloy tempers or conditions may be referred to. To understand the description of the most commonly used alloy tempers, please refer to "American National Standards (ANSI) H35 on Alloy and Temper Designation Systems". The F state or temper refers to the aluminum alloy as produced. The O state or temper refers to the aluminum alloy after annealing. The Hxx state or temper (also referred to herein as the H temper) refers to the non-heat treated aluminum alloy after cold rolling, with or without heat treatment (e.g., annealing). Suitable H tempers include the HX1, HX2, HX3, HX4, HX5, HX6, HX7, HX8, or HX9 tempers. The T1 state or temper refers to the aluminum alloy that has been cooled from hot working and naturally aged (e.g., at room temperature). The T2 state or temper refers to the aluminum alloy that has been cooled from hot working, cold worked, and naturally aged. The T3 condition or temper refers to an aluminum alloy that has been solution heat treated, cold worked, and naturally aged. The T4 condition or temper refers to an aluminum alloy that has been solution heat treated and naturally aged. The T5 condition or temper refers to an aluminum alloy that has been cooled from hot working and artificially aged (at high temperature). The T6 condition or temper refers to an aluminum alloy that has been solution heat treated and artificially aged. The T7 condition or temper refers to an aluminum alloy that has been solution heat treated and artificially overaged. The T8x condition or temper refers to an aluminum alloy that has been solution heat treated, cold worked, and artificially aged. The T9 condition or temper refers to an aluminum alloy that has been solution heat treated, artificially aged, and cold worked. The W condition or temper refers to an aluminum alloy after solution heat treatment.
[0030] As used herein, the terms "cast metal product," "cast product," "cast aluminum alloy product," and the like are used interchangeably and refer to products produced by direct chill casting (including direct chill co-casting) or semi-continuous casting, continuous casting (including, for example, by use of a twin belt caster, twin roll caster, block caster, or any other continuous casting machine), electromagnetic casting, hot top casting, or any other casting process.
[0031] As used herein, the meaning of "room temperature" can include temperatures between about 15° C. and about 30° C., such as about 15° C., about 16° C., about 17° C., about 18° C., about 19° C., about 20° C., about 21° C., about 22° C., about 23° C., about 24° C., about 25° C., about 26° C., about 27° C., about 28° C., about 29° C., or about 30° C. As used herein, the meaning of "ambient conditions" can include temperatures at about room temperature, relative humidity between about 20% and about 100%, and atmospheric pressure between about 975 millibars (mbar) and about 1050 mbar. For example, the relative humidity may be about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, about 41%, about 42%, about 43%, about 44%, about 45%, about 46%, about 47%, about 48%, about 49%, about 50%, about 51%, about 52%, about 53%, about 54%, about 55%, about 56%, about 57%, about 58%, about 59%, about 60%, about 61%. , about 62%, about 63%, about 64%, about 65%, about 66%, about 67%, about 68%, about 69%, about 70%, about 71%, about 72%, about 73%, about 74%, about 75%, about 76%, about 77%, about 78%, about 79%, about 80%, about 81%, about 82%, about 83%, about 84%, about 85%, about 86%, about 87%, about 88%, about 89%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99%, about 100%, or anywhere therebetween. For example, the air pressure can be about 975 mbar, about 980 mbar, about 985 mbar, about 990 mbar, about 995 mbar, about 1000 mbar, about 1005 mbar, about 1010 mbar, about 1015 mbar, about 1020 mbar, about 1025 mbar, about 1030 mbar, about 1035 mbar, about 1040 mbar, about 1045 mbar, about 1050 mbar, or anywhere therebetween.
[0032] All ranges disclosed herein should be understood to encompass all subranges subsumed therein. For example, the stated range "1-10" should be considered to encompass all subranges between a minimum value of 1 and a maximum value of 10, inclusive. That is, all subranges begin with a minimum value of 1 or greater (e.g., 1-6.1) and end with a maximum value of 10 or less (e.g., 5.5-10). Unless otherwise stated, the expression "maximum," when referring to a compositional amount of an element, means that the element is optional and includes a zero percent composition of that particular element. Unless otherwise stated, all compositional percentages are weight percent (wt.%).
[0033] As used herein, the meanings of "a," "an," and "the" include singular and plural references unless the context clearly indicates otherwise.
[0034] In the following examples, aluminum alloy products and their components may be described in terms of their elemental composition in weight percent (wt.%), atomic percentage (at%), or mole percentage (mol.%). In each alloy, if the maximum wt.% is 1% relative to the sum of all impurities, the remaining portion is aluminum (e.g., less than or about 0.15%, 0.25%, 0.5%, 0.75%, or 1%). In some examples, impurities refer to unspecified elemental components other than those specifically indicated for a particular alloy or composition. In some examples, aluminum alloys or composites including aluminum and one or more other components that may be present in amounts up to 30 mol%, 40 mol%, or 50 mol% are described herein.
[0035] Accompanying elements (e.g., grain refiners and deoxidizers), or other additives, may be present in the present invention and may themselves add other properties without departing from or significantly altering the properties of the alloys described herein or the alloys illustrated herein.
[0036] Inevitably impurities (including materials or elements) may be present in small amounts in the alloy due to the inherent properties of aluminum or due to dissolution from contact with processing equipment. As explained, some alloys may contain up to about 0.25 wt.% of any element in addition to the alloying elements, incidental elements, and inevitable impurities.
[0037] Method for manufacturing an aluminum alloy product The aluminum alloy products described herein (e.g., aluminum alloy foils or aluminum-based foils) can be prepared using any suitable method, such as by casting, homogenizing, hot rolling, cold rolling, heat treating, forming, etc., of the aluminum alloy to produce the aluminum alloy product.
[0038] FIG. 1 illustrates an overview of an exemplary method for producing an aluminum alloy product. The method of FIG. 1 begins at 105, where an aluminum alloy 106 is cast to form a cast aluminum alloy product 107, such as an ingot or other cast product. At 110, the cast aluminum alloy product 107 is homogenized to form a homogenized aluminum alloy product 111. At 115, the homogenized aluminum alloy product 111 is subjected to one or more hot rolling passes and / or one or more cold rolling passes to form a rolled aluminum alloy product 112. The rolled aluminum alloy product 112 may represent an aluminum alloy article (e.g., an aluminum alloy plate, an aluminum alloy shade, or an aluminum alloy sheet). Optionally, the rolled aluminum alloy product 112 is subjected to additional processing steps, as described below, to form an aluminum alloy article.
[0039] Non-limiting examples of casting processes include a direct chill (DC) casting process or a continuous casting (CC) process. For example, FIG. 1 shows a schematic diagram of a DC casting process at 105, although other casting processes can be used. A continuous casting system can include a pair of movable opposing casting surfaces (e.g., movable opposing belts, rolls, or blocks), a casting cavity between the pair of movable opposing casting surfaces, and a molten metal injector. The molten metal injector can have an end opening through which molten metal can exit the molten metal injector and be injected into the casting cavity.
[0040] The cast aluminum alloy product (e.g., cast ingot, cast slab, or other cast product) may be processed by any desired technique. Optionally, this processing step may be used to prepare a rolled aluminum alloy product (e.g., aluminum alloy sheet). Examples of optional processing steps include, but are not limited to, homogenization, hot rolling, cold rolling, annealing, solution heat treatment, and pre-aging.
[0041] In the homogenization step, the cast product may be heated to a temperature ranging from about 400°C to about 600°C. For example, the cast product may be heated to a temperature of about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, about 450°C, about 460°C, about 470°C, about 480°C, about 490°C, about 500°C, about 510°C, about 520°C, about 530°C, about 540°C, about 550°C, about 560°C, about 570°C, about 580°C, about 590°C, or about 600°C. The product may then be soaked (i.e., held at the indicated temperature) for a period of time to form a homogenized product. In some examples, the total time for the homogenization step (including the heating and soaking stages) may be up to 24 hours. For example, the homogenization step may involve heating and soaking the product to a maximum of 500°C-600°C for a total time of up to 18 hours. Optionally, the homogenization step may involve heating and soaking the product to less than 490°C for a total time of more than 18 hours. In some cases, the homogenization step may involve multiple processes. In some non-limiting examples, the homogenization step may involve heating the cast product to a first temperature for a first time, followed by heating to a second temperature for a second time. For example, the cast product may be heated to about 465°C for about 3.5 hours, and then heated to about 480°C for about 6 hours.
[0042] Following the homogenization step, a hot rolling step can optionally be performed. Before starting the hot rolling, the homogenized product can be cooled to a temperature between 300° C. and 450° C. For example, the homogenized product can be cooled to a temperature between 325° C. and 425° C. or between 350° C. and 400° C. The homogenized product is then hot rolled at a temperature of 300°C to 450°C to form a hot rolled plate, hot rolled shade, or hot rolled sheet having a gauge of 3mm to 200mm (e.g., 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm, 200mm, or anywhere therebetween).
[0043] Optionally, the cast product may be a continuous cast product that may be cooled to a temperature of 300° C. to 450° C. For example, the continuous cast product may be cooled to a temperature of 325° C. to 425° C. or 350° C. to 400° C. The continuous cast product is then hot rolled at a temperature of 300°C to 450°C to form a hot rolled plate, hot rolled shade, or hot rolled sheet having a gauge of 3mm to 200mm (e.g., 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 15mm, 20mm, 25mm, 30mm, 35mm, 40mm, 45mm, 50mm, 55mm, 60mm, 65mm, 70mm, 75mm, 80mm, 85mm, 90mm, 95mm, 100mm, 110mm, 120mm, 130mm, 140mm, 150mm, 160mm, 170mm, 180mm, 190mm, 200mm, or anywhere therebetween). During hot rolling, the temperature and other operating parameters can be controlled so that the temperature of the hot rolled intermediate product leaving the hot rolling mill is 470°C or less, 450°C or less, 440°C or less, or 430°C or less.
[0044] The cast, homogenized, or hot rolled product can optionally be cold rolled using a cold rolling mill to produce a thinner product (e.g., cold rolled sheet or foil). The cold rolled product can optionally have a gauge between about 0.5-10 mm, e.g., about 0.7-6.5 mm. Optionally, the cold rolled product can have a gauge of 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, or 10.0 mm. Cold rolling can be performed to a final gauge thickness that represents a gauge reduction of up to 85% (e.g., a reduction of up to 10%, up to 20%, up to 30%, up to 40%, up to 50%, up to 60%, up to 70%, up to 80%, or up to 85%) compared to the gauge before cold rolling began. In the case of foils, cold rolling can be performed to the final thickness of the foil (e.g., less than 0.2 mm). Optionally, an intermediate annealing step can be performed during the cold rolling steps. For example, a first cold rolling process is applied, followed by an annealing process (intermediate annealing), followed by a second cold rolling process. The intermediate annealing step can be performed at a temperature between about 300°C and about 450°C (e.g., about 310°C, about 320°C, about 330°C, about 340°C, about 350°C, about 360°C, about 370°C, about 380°C, about 390°C, about 400°C, about 410°C, about 420°C, about 430°C, about 440°C, or about 450°C). In some cases, the intermediate annealing step includes multiple processes. In some non-limiting examples, the intermediate annealing step includes heating the partially cold rolled product to a first temperature for a first time, followed by heating to a second temperature for a second time. For example, the partially cold rolled product can be heated to about 410°C for about 1 hour, and then heated to about 330°C for about 2 hours.
[0045] The cast, homogenized, or rolled product may then optionally undergo a solution heat treatment step. The solution heat treatment step may be any suitable treatment of the product that results in solution of the soluble particles. The cast, homogenized, or rolled product may be heated to a peak metal temperature (PMT) of up to 590°C (e.g., 400°C-590°C) and soaked at the PMT for a period of time to form a hot product. For example, the cast, homogenized, or rolled product may be soaked at 480°C for a soak time of up to 30 minutes (e.g., 0 seconds, 60 seconds, 75 seconds, 90 seconds, 5 minutes, 10 minutes, 20 minutes, 25 minutes, or 30 minutes). After heating and soaking, the hot product is quenched at a rate of more than 200°C / s to a temperature of 500-200°C to form a heat treated product. In one example, the hot product is cooled to a temperature between 450°C and 200°C at a quench rate of greater than 200°C / sec. Optionally, in other cases, the cooling rate can be faster. Optionally, in other cases, the temperature can be lower. In one example, the hot product is cooled to a temperature between 450°C and 200°C at a quench rate of greater than 200°C / sec.
[0046] After quenching, the heat treated product can optionally be pre-aged by reheating before winding. Pre-aging can be performed at a temperature of about 70°C to about 125°C for a period of time up to 6 hours. For example, pre-aging can be performed at a temperature of about 70°C, about 75°C, about 80°C, about 85°C, about 90°C, about 95°C, about 100°C, about 105°C, about 110°C, about 115°C, about 120°C, or about 125°C. Optionally, pre-aging can be performed for about 30 minutes, about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours. Pre-aging can be performed by passing the heat treated product through a heating device, such as a device that emits radiant heat, convective heat, induction heat, infrared heat, or the like.
[0047] The cast products described herein can be used to produce products in the form of sheets (including foils), plates, or other suitable products. For example, plates including the products described herein can be prepared by a hot rolling step after the ingot is treated in a homogenization step or the product is cast in a continuous caster. In the hot rolling step, the cast products can be hot rolled to 200 mm thickness gauge or less (e.g., about 10 mm to about 200 mm). For example, the cast products can be hot rolled into plates having a final gauge thickness of about 10 mm to about 175 mm, about 15 mm to about 150 mm, about 20 mm to about 125 mm, about 25 mm to about 100 mm, about 30 mm to about 75 mm, or about 35 mm to about 50 mm. In some cases, the plates may be rolled into thinner metal products (e.g., sheets or foils).
[0048] Other techniques besides casting and rolling can be used to prepare metal products such as aluminum alloy or other foils. In some examples, powder-based sintering or melting processes can be used, optionally in conjunction with rolling or other processing processes. In some examples, metal products can be prepared using selective laser melting, direct metal laser sintering, laser powder bed melting, or other additional manufacturing techniques. In some examples, metal products prepared by powder-based additive manufacturing or composite engineering processes can be subjected to rolling to at least partially consolidate the foil and / or to produce foils from the metal products.
[0049] Exemplary Metals and Metal Alloys Described herein are methods for preparing and using metals and metal alloys, including, inter alia, aluminum, aluminum alloys, resultant metals and metal alloys, and apparatus for incorporating metals and metal alloys. In some examples, the metals used in the methods described herein include aluminum alloys, such as 1xxx series aluminum alloys, 2xxx series aluminum alloys, 3xxx series aluminum alloys, 4xxx series aluminum alloys, 5xxx series aluminum alloys, 6xxx series aluminum alloys, 7xxx series aluminum alloys, or 8xxx series aluminum alloys. In some examples, the materials used in the methods described herein include non-ferrous materials, including aluminum, aluminum alloys, and aluminum-based composite materials, such as aluminum and non-aluminum components (silicon, tin, indium, gallium, antimony, lead, nickel, copper, zinc, carbon, germanium, silver, etc.). In some examples, aluminum alloys containing iron are useful in the methods and apparatus described herein.
[0050] As a non-limiting example, exemplary 1xxx series aluminum alloys for use in the methods described herein can include AA1100, AA1100A, AA1200, AA1200A, AA1300, AA1110, AA1120, AA1230, AA1230A, AA1235, AA1435, AA1145, AA1345, AA1445, AA1150, AA1350, AA1350A, AA1450, AA1370, AA1275, AA1185, AA1285, AA1385, AA1188, AA1190, AA1290, AA1193, AA1198, or AA1199.
[0051] Non-limiting examples of 2xxx series aluminum alloys for use in the methods and apparatus described herein include AA2001, A2002, AA2004, AA2005, AA2006, AA2007, AA2007A, AA2007B, AA2008, AA2009, AA2010, AA2011, AA2011A, AA2111, AA2111A, AA2111B, AA2012, AA2013, AA2014, AA2014A, AA2214, AA2015, AA2016, AA2017, AA2017A, AA2117, AA2018, AA2218, AA2618, AA2618A, AA 2219, AA2319, AA2419, AA2519, AA2021, AA2022, AA2023, AA2024, AA2024A, AA2124, AA2224, AA2224A, AA2324 , AA2424, AA2524, AA2624, AA2724, AA2824, AA2025, AA2026, AA2027, AA2028, AA2028A, AA2028B, AA2028C, A A2029, AA2030, AA2031, AA2032, AA2034, AA2036, AA2037, AA2038, AA2039, AA2139, AA2040, AA2041, AA2044, AA2045, AA2050, AA2055, AA2056, AA2060, AA2065, AA2070, AA2076, AA2090, AA2091, AA2094, AA2095, AA2195, AA2295, AA2196, AA2296, AA2097, AA2197, AA2297, AA2397, AA2098, AA2198, AA2099, or AA2199.
[0052] Non-limiting examples of 3xxx series aluminum alloys for use in the methods and apparatus described herein include AA3002, AA3102, AA3003, AA3103, AA3103A, AA3103B, AA3203, AA3403, AA3004, AA3004A, AA3104, AA3204, AA3304, AA3005, AA3005A, AA3105, AA3105A, AA3105B, AA3007, AA3107, AA3207, AA3207A, AA3307, AA3009, AA3010, AA3110, AA3011, AA3012, AA3012A, AA3013, AA3014, AA3015, AA3016, AA3017, AA3019, AA3020, AA3021, AA3025, AA3026, AA3030, AA3130, or AA3065.
[0053] Non-limiting examples of 4xxx series aluminum alloys for use in the methods and apparatus described herein can include AA4004, AA4104, AA4006, AA4007, AA4008, AA4009, AA4010, AA4013, AA4014, AA4015, AA4015A, AA4115, AA4016, AA4017, AA4018, AA4019, AA4020, AA4021, AA4026, AA4032, AA4043, AA4043A, AA4143, AA4343, AA4643, AA4943, AA4044, AA4045, AA4145, AA4145A, AA4046, AA4047, AA4047A, or AA4147.
[0054] Non-limiting examples of 5xxx series aluminum alloys for use in the methods and apparatus described herein include AA5182, AA5183, AA5005, AA5005A, AA5205, AA5305, AA5505, AA5605, AA5006, AA5106, AA5010, AA5110, AA5110A, AA5210, AA5310, AA5016, AA5017, AA5018, AA5018A, AA5019, AA5019A , AA5119, AA5119A, AA5021, AA5022, AA5023, AA5024, AA5026, AA5027, AA5028, AA5040, AA5140, AA5041, AA5042, AA5043, AA5049, AA5149, AA5249, AA5349, AA5449, AA5449A, AA5050, AA5050A, AA5050C, AA5150, AA5051, AA5051A, AA5151, AA525 1, AA5251A, AA5351, AA5451, AA5052, AA5252, AA5352, AA5154, AA5154A, AA5154B, AA5154C, AA5254, AA5354, AA5454, AA5 554, AA5654, AA5654A, AA5754, AA5854, AA5954, AA5056, AA5356, AA5356A, AA5456, AA5456A, AA5456B, AA5556, AA5556A, AA5556B, AA5556C, AA5257, AA5457, AA5557, AA5657, AA5058, AA5059, AA5070, AA5180, AA5180A, AA5082, AA5182, AA5083, AA5183, AA5183A, AA5283, AA5283A, AA5283B, AA5383, AA5483, AA5086, AA5186, AA5087, AA5187, or AA5088.
[0055] Non-limiting examples of 6xxx series aluminum alloys for use in the methods and apparatus described herein include AA6101, AA6101A, AA6101B, AA6201, AA6201A, AA6401, AA6501, AA6002, AA6003, AA6103, AA6005, AA6005A, AA6005B, AA6005C, AA6105, AA6205, AA6305, AA6006, AA6106, AA6206 , AA6306, AA6008, AA6009, AA6010, AA6110, AA6110A, AA6011, AA6111, AA6012, AA6012A, AA6013, AA6113, AA6014, AA6 015, AA6016, AA6016A, AA6116, AA6018, AA6019, AA6020, AA6021, AA6022, AA6023, AA6024, AA6025, AA6026, AA6027, AA 6028, AA6031, AA6032, AA6033, AA6040, AA6041, AA6042, AA6043, AA6151, AA6351, AA6351A, AA6451, AA6951, AA6053, AA6055, AA6056, AA6156, AA6060, AA6160, AA6260, AA6360, AA6460, AA6460B, AA6560, AA6660, AA6061, AA6061A, AA62 AA61, AA6361, AA6162, AA6262, AA6262A, AA6063, AA6063A, AA6463, AA6463A, AA6763, A6963, AA6064, AA6064A, AA6065, AA6066, AA6068, AA6069, AA6070, AA6081, AA6181, AA6181A, AA6082, AA6082A, AA6182, AA6091, or AA6092.
[0056] Non-limiting examples of 7xxx series aluminum alloys for use in the methods and apparatus described herein include AA7011, AA7019, AA7020, AA7021, AA7039, AA7072, AA7075, AA7085, AA7108, AA7108A, AA7015, AA7017, AA7018, AA7019A, AA7024, AA70 25, AA7028, AA7030, AA7031, AA7033, AA7035, AA7035A, AA7046, AA7046A, AA7003, AA7004, AA700 5, AA7009, AA7010, AA7011, AA7012, AA7014, AA7016, AA7116, AA7122, AA7023, AA7026, AA7029, AA 7129, AA7229, AA7032, AA7033, AA7034, AA7036, AA7136, AA7037, AA7040, AA7140, AA7041, AA704 9, AA7049A, AA7149, AA7204, AA7249, AA7349, AA7449, AA7050, AA7050A, AA7150, AA7250, AA7055 , AA7155, AA7255, AA7056, AA7060, AA7064, AA7065, AA7068, AA7168, AA7175, AA7475, AA7076, AA7178, AA7278, AA7278A, AA7081, AA7181, AA7185, AA7090, AA7093, AA7095, or AA7099.
[0057] Non-limiting examples of 8xxx series aluminum alloys for use in the methods and apparatus described herein include AA8005, AA8006, AA8007, AA8008, AA8010, AA8011, AA8011A, AA8111, AA8211, AA8112, AA8014, AA8015, AA8016, AA8017, AA8018, AA8019, AA8 AA8076, AA8076A, AA8176, AA8077, AA8177, AA8079, AA8090, AA8091, or AA8093.
[0058] Methods of using the disclosed aluminum alloy products The aluminum alloy products described herein can be used in battery applications. For example, the disclosed aluminum alloy products can be used as current collectors and / or electrode materials for batteries or electrochemical cells.
[0059] The aluminum alloy products and methods described herein can also be used in other electronics applications. For example, the aluminum alloy products and methods described herein can be used to make housings for electronic devices that contain batteries. In some examples, the aluminum alloy products can be used to make housings for mobile phones (e.g., smartphones), tablet bottom chassis, single and multi-cell batteries, and outer casings for other portable electronics.
[0060] As mentioned above, solid-state electrochemical cells incorporating solid electrolytes can advantageously incorporate aluminum materials as the anode active material. As an alloyed electrode, aluminum can exhibit higher energy storage density than commonly used anode materials for lithium-ion batteries, such as graphite, because aluminum has a higher storage potential relative to lithium than graphite. Although the storage capacity of aluminum may not be as high as metallic lithium, aluminum alloyed anodes provide safer operation of rechargeable or secondary batteries compared to lithium metal batteries, as they are not susceptible to dendrite formation.
[0061] Furthermore, avoiding the use of graphite as the anode material can not only increase the anode storage capacity, but also limit the use of wet processing, since the aluminum-based alloyed anode can be incorporated as a film or foil of material and does not need to be a slurry deposited on a current collector. In some cases, the aluminum-based alloyed anode allows for use as the anode material without a current collector, although traditional anode current collectors such as copper foils can also be used. In some cases, the current collector can include an aluminum foil, such as an aluminum foil that is different from the active material of the anode. In some examples, a protected aluminum foil can be used as the anode current collector as described in International Application Publication No. WO2021 / 184035, which is incorporated herein by reference.
[0062] Additionally, the incorporation of aluminum-based materials as active materials into solid-state electrochemical cells allows for the incorporation of recycled content directly into the electrodes of the electrochemical cell. For example, the anode active material of the solid-state electrochemical cells described herein can include aluminum alloys that incorporate significant amounts of recycled content, such as up to 10%, up to 20%, up to 30%, up to 40% or more.
[0063] The use of solid electrolyte components can further enhance the safety, manufacturability, and other properties of the battery system. Lithium-ion batteries typically incorporate liquid organic solvents, such as carbonate solvents, into the electrolyte. Such solvents are typically flammable and undergo undesirable side reactions at the surface of the anode active material at the potentials of interest. These side reactions can result in the formation of a solid electrolyte interfacial (SEI) layer that degrades performance and reduces capacity.
[0064] The use of liquid electrolytes with aluminum-based active materials can exacerbate the formation of the SEI layer because aluminum-based active materials undergo volume changes when they absorb or release lithium ions. As the active material absorbs lithium, it expands, disrupting any SEI material on the surface of the active material and exposing new active material to the liquid electrolyte, which can undergo further reactions with the exposed active material and form additional SEI material. Thus, liquid electrolytes used with aluminum-based active materials can allow the accumulation of SEI material above the active material.
[0065] However, such build-up of SEI material may not occur when solid electrolytes are used. For example, solid electrolytes are used with lithium silver germanium sulfate materials (e.g., Li 6 P.S. 5 The electrolyte may comprise a solid electrolyte, such as a ceramic-type sulfate material, such as Cr(Cl), etc. When such a solid electrolyte encounters a volume expansion of the anode active material through the absorption of lithium, the solid electrolyte cannot flow and penetrate into the cracks and interfaces of the exposed new active material, limiting the formation of the SEI material.
[0066] To ensure that good electrical and ionic communication is maintained during charging or discharging, and to account for volumetric contraction or expansion due to release or absorption of lithium atomic ions, pressure can be applied between the solid electrolyte and the aluminum-based active anode material. Such pressure can be applied as a stack pressure between the anode and cathode, with the solid electrolyte between the anode and cathode. The stack pressure can be applied through a casing or other components. Exemplary stack pressures can range from 0.1 MPa to 30 MPa.
[0067] 2 shows a schematic diagram of an exemplary solid-state electrochemical cell 200 including an anode active material 205, a cathode active material 210, a solid electrolyte 215, an anode current collector 220, and a cathode current collector 225. In a conventional lithium-ion battery system, the cathode current collector includes high-purity aluminum foil, the cathode active material includes lithium metal oxide, a porous non-conductive material soaked with a liquid electrolyte including an organic solvent and a lithium salt is disposed between the anode active material and the cathode active material, the anode active material includes graphite, and the anode current collector includes copper foil. Some of these materials may be used with solid-state electrochemical cells, while others, such as liquid electrolytes, may not be used.
[0068] For example, the cathode active material 210 and the cathode current collector 225 may incorporate materials used in conventional battery systems. Optionally, the cathode current collector 225 may include aluminum, such as in the form of an aluminum alloy foil. In some cases, the cathode current collector 225 may include a high purity aluminum alloy, such as one containing 99.00% or more by weight Al. The use of a high purity aluminum alloy is useful to maintain the electrical conductivity of the cathode current collector 225 at the highest possible level. The cathode active material 210 may include any suitable cathode active material, including, but not limited to, an alkali metal host material, such as lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, or lithium metal cobalt oxide, or an alkali metal-transition metal oxide cathode active material.
[0069] The anode active material 205 may include, for example, an alkali metal alloyed anode. Lithium can be alloyed with aluminum at the potential encountered at the anode, and lithium ions can be reduced during charging and incorporated as an alloy into the bulk of the aluminum material. During discharge, lithium can be oxidized and released as lithium ions from the alkali metal alloyed anode. The aluminum used in the anode active material 205 may be a foil, such as a foil comprising aluminum or an aluminum alloy, optionally a composite or mixed metal foil comprising one or more other metals or semiconductors, such as silicon, tin, indium, gallium, antimony, lead, nickel, copper, zinc, carbon, germanium, silver, optionally in amounts up to 50 mol %. As described herein, the foils can be processed using metal casting and metal rolling processes, although other techniques, including powder-based sintering processes, or laser melting processes, such as laser powder bed melting techniques, can also be used to prepare the foils. The anode active material may exhibit a specific capacity of from about 300 mAh / g to about 1000 mAh / g or more, such as 300 mAh / g to 350 mAh / g, 400 mAh / g to 450 mAh / g, 450 mAh / g to 500 mAh / g, 500 mAh / g to 550 mAh / g, 550 mAh / g to 600 mAh / g, 600 mAh / g to 650 mAh / g, 650 mAh / g to 700 mAh / g, 700 mAh / g to 750 mAh / g, 750 mAh / g to 800 mAh / g, 800 mAh / g to 850 mAh / g, 850 mAh / g to 900 mAh / g, 900 mAh / g to 950 mAh / g, or 950 mAh / g to 1000 mAh. In some instances, the specific capacity may still be higher, such as when other components having higher specific capacity are included in the anode active material, such as silicon.
[0070] The anode active material 205 may include an aluminum alloy, or a multi-component system, such as a eutectic alloy, a solid solution alloy, a mixed metal system, or a composite particle system. In some examples, the anode active material 205 may include a multi-component foil including aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver. In some examples, the amount of aluminum in the anode active material 205 can be from about 40% to about 100% by weight aluminum, such as 40% to 45% by weight, 45% to 50% by weight, 50% to 55% by weight, 55% to 60% by weight, 60% to 65% by weight, 65% to 70% by weight, 70% to 75% by weight, 75% to 80% by weight, 80% to 85% by weight, 85% to 90% by weight, 90% to 95% by weight, 95% to 99% by weight, 99% to 99.9% by weight, or 99.9% to 99.99% by weight. In some examples, the amount of non-aluminum elements, such as one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver, may be about 0.1 wt.% to about 60 wt.% or less than about 1 wt.%, such as 0.1 wt.% to 0.5 wt.%, 0.5 wt.% to 1 wt.% to 2 wt.%, 2 wt.% to 5 wt.%, 5 wt.% to 10 wt.%, 10 wt.% to 15 wt.%, 15 wt.% to 20 wt.%, 20 wt.% to 25 wt.%, 25 wt.% to 30 wt.%, 30 wt.% to 35 wt.%, 35 wt.% to 40 wt.%, 40 wt.% to 45 wt.%, 45 wt.% to 50 wt.%, 50 wt.% to 55 wt.%, or 55 wt.% to 60 wt.%. In some examples, the anode active material 205 may include a composite material including a first plurality of aluminum or aluminum alloy particles and a second plurality of particles selected from at least one of metallic or non-metallic particles. Additional details regarding composite anodes are described in U.S. Provisional Application No. 63 / 261,216, which is incorporated herein by reference.
[0071] The anode current collector 220 may comprise any suitable material, such as copper, or other conductive material, such as aluminum. Copper may be beneficial for use as the anode current collector 220 because it is unreactive and highly electrically conductive at the potentials of interest in lithium battery systems. Although aluminum can alloy with lithium at the potentials of interest, making it useful as an anode active material 205, such properties may not be desirable for aluminum to be used as the anode current collector 220. However, aluminum may also be used as a highly conductive material and may be constructed as a foil, so in some instances aluminum may be used as the anode current collector 220. Optionally, when the anode active material 205 comprises a metal foil, the anode current collector 220 may not be used, since an electrical connection may be established directly with the anode active material 205 to provide for the conduction of electrons to and from an external circuit (e.g., a load or power source). In some cases, aluminum may be used as the anode current collector 220 in the form of a protected aluminum foil.
[0072] The anode current collector 220 may also be fabricated to have an engineered structure. By designing the structure, the structure may include additional space and microporous structure. Without being bound by theory, such additional space and / or microporous structure may compensate for volume changes within the anode current collector 220. To form the engineered structure, various methods may be used, including powder metallurgy, forming microporous or nanoporous structures by additive manufacturing, using metal foams, forming perforations by laser etching or deep etching, dealloying (e.g., chemical dealloying), or other methods. In some examples, the engineered structure may be processed, for example, by rolling, to at least partially consolidate the foil or otherwise produce a foil from the engineered structure. In some examples, the engineered structure may include a solid aluminum-based or aluminum alloy-based structure (e.g., foil) or may be bonded, joined, or adhered as a solid substrate to a solid aluminum-based or aluminum alloy-based structure (e.g., foil). In some examples, the engineered structure may be bonded, joined, or adhered to a current collector, such as, for example, a copper current collector, or a foil-based current collector, such as a protected or coated aluminum or aluminum alloy current collector (e.g., aluminum or aluminum foil coated with Fe, TiN, Ni, etc.). Examples of aluminum-based current collectors, including protected or coated aluminum current collectors, are described in PCT International Application No. PCT / US2021 / 070250, which is incorporated herein by reference.
[0073] Any suitable solid electrolyte 215 may be used in the solid-state electrochemical cell 200. For example, the solid electrolyte 215 may include an ionically conductive and electrically insulating material, such as an inorganic solid electrolyte. In some cases, the solid electrolyte 215 may include a solid polymer electrolyte, a composite polymer electrolyte, a polymer gel electrolyte, or a gel electrolyte, but in some examples, the solid electrolyte 215 explicitly includes an inorganic solid electrolyte rather than a solid polymer electrolyte, a composite polymer electrolyte, or a gel electrolyte. Inorganic solid electrolytes include, but are not limited to, crystalline, glassy, or ceramic ionically conductive materials (e.g., alkali metal ion conducting materials). Exemplary solid electrolytes include lithium superionic conductors (LISICON), silver germanium sulfate materials, (e.g., Li 6 P.S. 5 Cl), doped garnet materials, (e.g., Li 7 La 3 Zr 2 O 12 , LLZO), Li 10 GeP 2 S 12 , and Li 10 SnP 2 S 12 Related materials such as lithium phosphate sulfide (e.g., Li 3 P.S. 4 ), or lithium oxynitride phosphorus (LIPON). Suitable materials for the solid electrolyte 215 have a specific resistance to alkali metal ions of about 10 -4 S / cm (e.g., 10 -4 It can exhibit ionic conductivity of 0.01 S / cm to 0.01 S / cm.
[0074] 3 shows a schematic diagram of another solid-state electrochemical cell 300. The solid-state electrochemical cell 300 may include similar or identical components to the solid-state electrochemical cell 300. For example, the solid-state electrochemical cell 300 may include an anode active material 305, a cathode active material 310, a solid electrolyte 315, an anode current collector 320, and a cathode current collector 325. Such components may include the same materials as described above.
[0075] The solid-state electrochemical cell 300 further includes a protective coating 335 surrounding the anode current collector 320. The use of the protective coating 335 may allow the anode current collector 320 to include a material that alloys with an alkali metal, such as aluminum, as a current collector without the anode current collector 320 suffering from detrimental effects that may occur during alloying. For example, the protective coating 335 may include a conductive material that blocks the permeation of lithium atoms, allowing the lithium atoms to conduct electrons to the anode current collector 320 while preventing them from reaching and alloying with the anode current collector 320. Exemplary materials and configurations for the protective coating 335 are described in International Publication No. WO 2021 / 184035. In one non-limiting example, the protective coating 335 includes an ionic coating.
[0076] The solid-state electrochemical cell 300 further includes an interface material 340 between the anode active material 305 and the solid electrolyte 315. In some examples, the interface material 340 corresponds to an SEI layer that may form during cycling of the solid-state electrochemical cell 300, or an artificial SEI. In other examples, the interface material 340 is another material disposed between the anode active material 305 and the solid electrolyte 315, such as a polymer coating, a carbon coating, or an inorganic coating. In some examples, the interface material 340 can improve contact between the anode active material 305 and the solid electrolyte 315 or provide improved ionic conductivity and / or provide a buffer for the absorption and / or release of lithium ions, for example. In some cases, the interface material 340 can prevent the formation of dendrites when the anode active material 305 is caused to absorb lithium beyond its alloying capacity.
[0077] Any suitable dimensions of the anode active material, anode current collector, cathode active material, cathode current collector, solid electrolyte, interfacial material, or protective coating may be used, without limitation. In some examples, the solid electrolyte may have a thickness of about 10 μm to about 300 μm, such as 10 μm to 20 μm, 20 μm to 30 μm, 30 μm to 40 μm, 40 μm to 50 μm, 50 μm to 75 μm, 75 μm to 100 μm, 100 μm to 125 μm, 125 μm to 150 μm, 150 μm to 175 μm, 175 μm to 200 μm, 200 μm to 250 μm, or 250 μm to 300 μm. In some examples, the anode or anode active material may have a thickness of about 5 μm to about 60 μm, such as 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 20 μm to 25 μm, 25 μm to 30 μm, 30 μm to 35 μm, 35 μm to 40 μm, 40 μm to 45 μm, 45 μm to 50 μm, 50 μm to 55 μm, or 55 μm to 60 μm.
[0078] The examples disclosed herein serve to further illustrate aspects of the present invention, but at the same time do not constitute any limitation thereof. On the contrary, it should be clearly understood that recourse may be had to various embodiments, modifications thereof, and equivalents, which may suggest themselves to those skilled in the art after reading the description herein, without departing from the spirit of the present invention. The examples and embodiments described herein may also utilize conventional procedures, unless otherwise indicated. Some procedures are described herein for illustrative purposes.
[0079] Example 1 This example details comparative testing of electrochemical cells, including solid-state electrochemical cells incorporating aluminum active anode material and solid electrolyte, and comparative cells incorporating aluminum active material and liquid electrolyte.
[0080] Solid-state electrochemical cells have the chemical formula LiNi 0.6 Mn 0.2 Co 0.2 O 2 The cathode was prepared using lithium nickel manganese cobalt oxide (NMC-622) and an aluminum alloy anode.6 P.S. 5 A Cl solid electrolyte was placed between the cathode and anode. As a reference cell, the same aluminum alloy-based anode was assembled into a half-cell with liquid electrolyte using a lithium metal counter electrode with a porous separator between the aluminum alloy-based anode and the lithium metal counter electrode soaked in an electrolyte of 1.0 M lithium bis(fluorosulfonyl)imide (LiFSI) and 1.0 M lithium difluoro(oxalic acid)borate (LiDFOB) in a 3:7 volume ratio in fluoroethylene carbonate:diethyl carbonate (FEC:DEC). The aluminum alloy-based anode was about 30 μm thick and 1 cm in diameter, and was either high purity aluminum or an aluminum alloy with 6 atomic % indium. The solid cell was cycled first at C / 40 for two cycles, then at C / 20 for three cycles, and at C / 10 for the remaining cycles. A stack pressure of about 24 MPa was applied to the solid cell.
[0081] The solid-state cell was cycled between 2.2 V and 4.0 V and the areal capacity (mAh cm -2 ) was monitored as a function of cycle number. The anode to cathode capacity ratio (N:P) was 1.44 for the solid-state cell in Figure 4 and 1.60 for the solid-state cell in Figure 7. The reference half-cell was charged to 3.0 mAh cm during each step of lithiating the aluminum alloy-based anode until the reference cell failed. -2 It was circulated and controlled to have an areal capacity.
[0082] Voltage vs. capacity curves are shown for the first, second, and tenth cycles for two exemplary solid-state electrochemical cells in Figures 4 and 7, and for the reference half-cell in Figure 10. A graph of capacity vs. cycle number is shown for two exemplary solid-state electrochemical cells in Figures 5 and 8, and for the reference half-cell in Figure 11. A graph of coulombic efficiency vs. cycle number is shown for two exemplary solid-state electrochemical cells in Figures 6 and 9, and for the reference half-cell in Figure 12. As shown in Figures 6 and 9, the exemplary solid-state electrochemical cells exhibited first cycle initial coulombic efficiency (ICE) of 58% and 86%. The reference cell exhibited a first cycle initial coulombic efficiency (ICE) of about 91%.
[0083] The exemplary solid-state electrochemical cells exhibited significantly higher coulombic efficiencies compared to the reference half-cells, with the coulombic efficiencies of the solid-state electrochemical cells generally exceeding 97% (and in the case of one of the solid-state cells exceeding 99% after 10 cycles), whereas the reference half-cells exhibited a peak around 8 or 10 cycles and then steadily declined until about 45 cycles, where a dramatic drop was observed.
[0084] Exemplary Aspects As used hereinafter, any reference to a series of embodiments (e.g., "Embodiments 1-4") or an unrecited group of embodiments (e.g., "any preceding or subsequent embodiments") should be understood as a disjunctive reference to each of those embodiments (e.g., "Embodiments 1-4" should be understood to be "Embodiments 1, 2, 3, or 4").
[0085] A first aspect is a solid-state battery comprising an anode including aluminum as an anode active material, a cathode, and a solid electrolyte between the anode and the cathode.
[0086] Example 2 is the solid-state battery of any preceding or subsequent example, wherein the anode comprises an aluminum-based alkali metal alloyed anode.
[0087] Example 3 is the solid-state battery of any preceding or subsequent example, wherein the alkali metal is lithium.
[0088] Example 4 is the solid-state battery of any preceding or subsequent example, wherein the anode comprises an aluminum alloy or a recycled content aluminum alloy.
[0089] Example 5 is the solid-state battery of any preceding or subsequent example, wherein the anode comprises an aluminum-based multicomponent foil, the aluminum-based multicomponent foil including aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
[0090] Example 6 is the solid-state battery of any preceding or subsequent example, wherein the anode comprises a foil including 40% to 99 weight percent aluminum and 30% to 60% by weight one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
[0091] Example 7 is the solid-state battery of any preceding or subsequent example, wherein the anode has a thickness between 5 μm and 60 μm.
[0092] Example 8 is the solid-state battery of any preceding or subsequent example, wherein the anode exhibits a specific capacity between 300 mAh / g and 1000 mAh / g.
[0093] Example 9 is the solid-state battery of any preceding or subsequent example, wherein the anode comprises a composite foil including a first plurality of aluminum or aluminum alloy particles and a second plurality of particles selected from at least one of metallic particles or non-metallic particles.
[0094] Example 10 is the solid-state battery of any preceding or subsequent example, wherein the solid electrolyte is an inorganic solid electrolyte.
[0095] In an eleventh aspect, the solid electrolyte is a lithium germanium sulfide material, Li 6 P.S. 5 Cl, Lithium superionic conductor (LISICON), doped garnet material, Li 7 La 3 Zr 2 O 12 (LLZO), Li 10 GeP 2 S 12 , Li 10 SnP 2 S 12 , lithium phosphate sulfide (Li 3 P.S. 4 ), lithium oxynitride phosphorus acid (LIPON), polymer solid electrolyte, or gel polymer electrolyte.
[0096] Example 12 is the solid-state battery of any preceding or subsequent example, wherein the solid electrolyte has a thickness between 10 μm and 300 μm.
[0097] Example 13 is any preceding or subsequent solid-state battery, wherein the cathode comprises an alkali metal host material or an alkali metal-transition metal oxide cathode active material.
[0098] Aspect 14 is a cathode comprising any one of lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, lithium cobalt oxide, a conversion cathode, FeS 2 , FeF 3 , a sulfur-based cathode, or any preceding or following solid-state battery containing sulfur.
[0099] Example 15 is any preceding or subsequent solid-state battery further comprising one or more of a cathode current collector in contact with the cathode, or an anode current collector in contact with the anode.
[0100] Example 16 is the solid-state battery of any preceding or subsequent example, wherein the anode current collector comprises a protected aluminum alloy foil.
[0101] Example 17 is any preceding or subsequent solid-state battery, wherein a stack pressure is applied between the anode and the cathode, and wherein the stack pressure is between 0.1 MPa and about 30 MPa.
[0102] Example 18 is any of the preceding or subsequent solid-state batteries, further comprising an interface material between the anode and the solid-state electrolyte.
[0103] Example 19 is any of the preceding or subsequent solid-state batteries, wherein the interface material comprises a solid electrolyte interface, an artificial solid electrolyte interface, a polymer coating, a carbon coating, or an inorganic coating.
[0104] Example 20 is a method of making a solid-state battery comprising: providing an anode, the anode comprising aluminum as an anode active material; providing a cathode; and disposing a solid electrolyte between the anode and the cathode.
[0105] Example 21 is the method of any preceding or subsequent example, wherein providing the anode comprises preparing an aluminum-based multicomponent foil, the aluminum-based multicomponent foil comprising aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
[0106] Example 22 is the method of any preceding or subsequent example, wherein preparing the aluminum-based multi-component foil comprises casting an aluminum-based multi-component product comprising aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to produce an aluminum-based multi-component product; and rolling the aluminum-based multi-component product into a foil.
[0107] Example 23 is the method of any preceding or subsequent example, wherein preparing the aluminum-based multi-component foil comprises obtaining a powder mixture of aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver, and subjecting the powder mixture to a laser powder bed fusion process to create an aluminum-based multi-component product.
[0108] Example 24 is the method of any preceding or subsequent example, wherein preparing the aluminum-based multicomponent foil comprises cumulatively roll-bonding aluminum or an aluminum alloy with a quantity of one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to create an aluminum-based multicomponent product.
[0109] Example 25 is the method of any preceding or subsequent example, wherein preparing the aluminum-based multi-component foil comprises using powder metallurgy, additive manufacturing, metal foam, forming perforations by laser or deep etching, or dealloying to form a microporous or nanoporous aluminum-based multi-component product.
[0110] Example 26. The method of any preceding or subsequent example, wherein preparing the aluminum-based multicomponent foil comprises rolling the aluminum-based multicomponent product into a foil.
[0111] Example 27 is the method of any preceding or subsequent example, further comprising one or more of contacting the anode with an anode current collector or contacting the cathode with a cathode current collector.
[0112] Example 28 is the method of any preceding or subsequent example, wherein the solid-state battery comprises the solid-state battery of any preceding example.
[0113] All patents and publications cited herein are incorporated by reference in their entirety. The foregoing description of the embodiments, including the illustrated embodiment, has been presented only for purposes of illustration and description and is not intended to be exhaustive or limited to the precise form disclosed. Numerous modifications, adaptations and uses thereof will be apparent to those skilled in the art.
Claims
1. 1. A solid-state battery comprising: an anode comprising aluminum as an anode active material; A cathode; a solid electrolyte between the anode and the cathode; The solid-state battery.
2. 10. The solid-state battery of claim 1, wherein the anode comprises an aluminum-based alkali metal alloyed anode.
3. 3. The solid-state battery of claim 2, wherein the alkali metal is lithium.
4. 10. The solid-state battery of claim 1, wherein the anode comprises an aluminum alloy, a recycled content aluminum alloy, or an aluminum braze alloy.
5. 10. The solid-state battery of claim 1, wherein the anode comprises an aluminum-based multicomponent foil, the aluminum-based multicomponent foil comprising aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
6. 10. The solid-state battery of claim 1, wherein the anode comprises a foil comprising 40% to 99% by weight aluminum and 30% to 60% by weight one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
7. 2. The solid-state battery of claim 1, wherein the anode has a thickness of 5 μm to 60 μm.
8. 10. The solid-state battery of claim 1, wherein the anode exhibits a specific capacity of 300 mAh / g to 1000 mAh / g.
9. 10. The solid-state battery of claim 1, wherein the anode comprises a composite foil including a first plurality of aluminum or aluminum alloy particles and a second plurality of particles selected from at least one of metallic or non-metallic particles.
10. The solid-state battery according to claim 1 , wherein the solid electrolyte is an inorganic solid electrolyte.
11. The solid electrolyte is a lithium silver germanium sulfide material, Li 6 P.S. 5 Cl, lithium superionic conductor (LISICON), doped garnet material, Li 7 La 3 Zr 2 O 12 (LLZO), Li 10 GeP 2 S 12 , Li 10 SnP 2 S 12 , lithium phosphate sulfide (Li 3 P.S. 4 ), lithium phosphorus oxynitride (LIPON), a polymer solid electrolyte, or a gel polymer electrolyte.
12. 2. The solid-state battery according to claim 1, wherein the solid electrolyte has a thickness of 10 μm to 300 μm.
13. 10. The solid-state battery of claim 1, wherein the cathode comprises an alkali metal host material or an alkali metal-transition metal oxide cathode active material.
14. The cathode may be selected from the group consisting of lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, lithium cobalt oxide, conversion cathode, FeS 2 , FeF 3 13. The solid-state battery of claim 1 comprising a cathode, a sulfur-based cathode, or sulfur.
15. a cathode current collector in contact with the cathode; or an anode current collector in contact with the anode; 13. The solid-state battery of claim 1, further comprising one or more of:
16. 16. The solid-state battery of claim 15, wherein the anode current collector comprises a protected aluminum alloy foil.
17. 2. The solid-state battery of claim 1, wherein a stack pressure is applied between the anode and the cathode, the stack pressure being between 0.1 MPa and 30 MPa.
18. 10. The solid-state battery of claim 1, further comprising an interface material between the anode and the solid electrolyte.
19. 10. The solid-state battery of claim 1, wherein the interface material comprises a solid electrolyte interface, an artificial solid electrolyte interface, a polymer coating, a carbon coating, or an inorganic coating.
20. 1. A method for manufacturing a solid-state battery, comprising: providing an anode, the anode comprising aluminum as an anode active material; providing a cathode; disposing a solid electrolyte between said anode and said cathode; The method comprising:
21. providing the anode, 21. The method of claim 20, comprising preparing an aluminum-based multi-component foil, said aluminum-based multi-component foil comprising aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver.
22. Preparing the aluminum-based multi-component foil comprises: casting an aluminum-based multi-component product comprising aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to produce an aluminum-based multi-component product; rolling said aluminum-based multi-component product into a foil; 22. The method of claim 21 , comprising:
23. Preparing the aluminum-based multi-component foil comprises: Obtaining a powder mixture of aluminum and one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver; subjecting said powder mixture to a laser powder bed fusion process to produce an aluminum-based multi-component product.
22. The method of claim 21 , comprising:
24. Preparing the aluminum-based multi-component foil comprises:
22. The method of claim 21, comprising cumulatively roll bonding aluminum or an aluminum alloy with a quantity of one or more of silicon, tin, indium, gallium, antimony, lead, nickel, copper, carbon, germanium, zinc, or silver to create an aluminum-based multi-component product.
25. Preparing the aluminum-based multi-component foil comprises: Forming microporous or nanoporous aluminum-based multi-component products using powder metallurgy, additive manufacturing, metal foams, laser or deep etching perforations, or dealloying 22. The method of claim 21 , comprising:
26. Preparing the aluminum-based multi-component foil comprises: rolling said aluminum-based multi-component product into a foil. The method of any one of claims 23 to 25, further comprising:
27. contacting the anode with an anode current collector; or contacting said cathode with a cathode current collector; 21. The method of claim 20, further comprising one or more of:
28. The method of any one of claims 20 to 27, wherein the solid-state battery comprises the solid-state battery of any one of claims 1 to 19.
Citation Information
Patent Citations
Negative electrode active material for electric device, negative electrode for electric device, and electric device
JP2012199213A
Solid-state battery and method for producing solid-state battery
WO2019151376A1
Negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode, battery, and aluminum clad metal laminate
WO2020075616A1
Negative-electrode active material for non-aqueous electrolyte secondary cell, negative electrode, cell, and laminate
WO2020105330A1
Laminate for lithium secondary battery
WO2021206118A1